Media Ownership Interference and the Covert Practice of Citizen Journalism among Mainstream Journalists in Nigeria - Christian Uzoma Igwe; Jammy Seigha Guanah; Edith Ijeoma Oshiokpu; Cordelia Omonigho Okpodu-Philip; Joyce Uzezi Edhere; Margaret Ifelunwa Eji (Budapest International Research and Critics University, 2025)
For journalists to function effectively, an atmosphere devoid of coercion and interference is needed, so as to afford them the opportunity and freedom to generate and distribute contents that are not biased, or value-laden. However, in recent times, journalists have had to contend with undue pressure from their employers (“pay masters”); this impede on fair and accurate reportage. The paper investigated the extent to which such interference in the operations of journalists, among others, could be a catalyst for alternative means of content dissemination, like citizen journalism among professional journalists in mainstream media. The Authoritarian and Democratic Participant Media theories were the theoretical foundations upon which this investigation was based. Using qualitative research method, 12 journalists (6 from Delta Broadcasting Service, Warri and 3 from Rize FM, and Crown FM, Warri respectively) were randomly selected. Interview was used as the instrument of data collection. Findings revealed that journalists were sometimes cowed to report issues that advance their owners' interest, and were also restricted from publishing content that may hinder their owners` interest. It also revealed that journalists sometimes engage in citizen journalism practice by circumventing such interference, and publishing through other social media platforms. The study recommended, among others, that journalists should be allowed to practice without pressure from their employers, and that they should stick to the ethics of their profession.